Multiple inductive effects of carbamazepine on combined therapy with paliperidone and amlodipine. (26th May 2015) - Akamine, Y.; Uehara, H.; Miura, M.; Yasui‐Furukori, N.; Uno, T.
Summary What is known and objective Carbamazepine is a potent inducer of cytochrome P450 3A and P‐glycoprotein. However, there are no reports of the effects of carbamazepine on more than one co‐administered drug. Case summary A 53‐year‐old female patient with schizophrenia and hypertension was on paliperidone 12 mg/day and amlodipine 5 mg/day. When carbamazepine was added to this prescription, the plasma concentrations of both drugs decreased dramatically in a dose‐dependent manner. Although the patient's psychotic symptoms did not change, as a result, her mean blood pressure increased to 160·1/103·6 mmHg from 138·4/91·4 mmHg at a carbamazepine dose of 600 mg/day. What is new and conclusion Theses cases show the effect of carbamazepine induction on two drugs simultaneously. Care is required when carbamazepine is added to drug regimens including paliperidone or amlodipine alone or together.